95.4k views
3 votes
Find the average rate of change between f(-7) and f(-1) in the function f(x)=x^2+2x -8

User Bsd
by
5.0k points

1 Answer

1 vote

Solve the equation by replacing x with -7 and then -1.

Then subtract the two to find the difference and divide that by the difference between -7 and -1.

f(-7) = -7^2 + 2(-7) -8 = 49 -14 -8 = 27

f(-1) = -1^2 + 2(-1) -8 = 1 -2 - 8 = -9

Difference between 27 and -9 = -36

Difference between -1 and -7 = -6

Rate of change = -36 /-6 = 6

User Muhammad Shahzad
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.